A Comparative Investigation on Clinical Characteristics in Pediatric Obstructive Sleep Apnea Based on Two Distinct Guidelines - Ji T; Long T; Li X; Xu Z; Zhao J; Wang G; Wang H; Li H; Zhang F; Zheng L; Wang S; Ni X (Nature and Science of Sleep)
Tingting Ji,1,* Ting Long,1,* Xiaodan Li,1,* Zhifei Xu,2 Jing Zhao,1 Guixiang Wang,1 Hua Wang,1 Hongbin Li,1 Fengzhen Zhang,1 Li Zheng,1 Shengcai Wang,1 Xin Ni1,3 1Department of Otolaryngology, Head and Neck Surgery, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, 100045, People’s Republic of China; 2Department of Respiratory Medicine, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, 100045, People’s Republic of China; 3Beijing Key Laboratory for Pediatric Diseases of Otolaryngology, Head and Neck Surgery, Beijing Pediatric Research Institute, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, 100045, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin Ni, Email nixin@bch.com.cn; Shengcai Wang, Email wsc820329@163.comObjective: To investigate the differences in assessment of clinical characteristics between children with obstructive sleep apnea (OSA) diagnosed according to the 2007 and 2020 guidelines and those without OSA, together with the relationships between polysomnography (PSG) parameters and cognitive tests scores in preschool and school-aged children with OSA.Methods: Eighty children were totally recruited and divided into OSA and non-OSA groups based on two distinct guidelines, with further subclassification into preschool and school-aged subgroups. Differences in PSG parameters and cognitive tests scores between groups and subgroups were analyzed and compared, followed by partial correlation analysis to determine the correlations between these characteristics.Results: Compared to the 2007 guideline, the 2020 guideline demonstrated more significant between-group differences in clinical characteristics assessments, especially verbal intelligent quotient (VIQ). For preschool children in the OSA and non-OSA subgroups, there were significant differences in PSG parameters and Block Diagram between the two guidelines. Additionally, the 2007 guideline showed difference in Picture Vocabulary, where the 2020 guideline exhibited differences in performance IQ (PIQ) and Geometric Figure For school-aged children in the OSA and non-OSA subgroups, both guidelines showed significant differences in PSG parameters, full-scale IQ (FIQ) and Block Diagram. The 2007 guideline had significant differences in PIQ, while the 2020 guideline had difference in VIQ. Furthermore, significant correlations were observed between PSG parameters and cognitive tests scores across different subgroups.Conclusion: The 2020 guideline has advantages in assessing the clinical characteristics of children with OSA, especially for verbal function, and is worthy of clinical promotion and application.Keywords: obstructive sleep apnea, children, guidelines, clinical characteristics